Encouraging the effectiveness of philanthropic institutions: Implementation of digital fundraising platform for Lazismu Medan City - Ahmad Afandi; Syahrul Amsari; Isra Hayati; Muhammad Arifin Lubis (Community Empowerment, 2024)
The use of information technology in fundraising has brought about a significant transformation in the operations of charitable organizations, enabling the expansion of reach and increasing the effectiveness of activities. Lazismu Medan City, a philanthropic institution in Indonesia, faces challenges in optimizing fundraising activities due to limited digital technology capacity and less effective marketing strategies. This community service aims to develop and implement a digital platform to enhance Lazismu's capacity in managing fundraising efficiently and transparently, accessible via lazismumedan.org. Methods for implementing the service include developing a platform, conducting comprehensive training for Lazismu administrators and volunteers, as well as enhancing skills in using digital technology to raise funds. The results of this service show a significant increase in the number of donations collected and the level of donor satisfaction, indicating increased capacity and transparency in Lazismu's fundraising activities.